Sistem Administrasi Keuangan PAUD Melati 03 Berbasis Web - Azzahra, Devita; Pramestia, Putri Fayza; Rivanda, Fairuz Javier; Haryono, Wasis (Yayasan Abdurrauf Cendekia Nusantara, 2025)
PAUD Melati 03 is an early childhood education institution committed to improving operational effectiveness through optimal financial administration management. To support this, a system is needed that can record and manage financial transactions efficiently and in a structured manner. This study aims to develop a web-based financial administration system to enhance the efficiency, transparency, and security of the institution's financial management. The system is designed using the Laravel 10 framework and Filament to facilitate various financial transactions, such as recording income and expenses, calculating teacher salaries based on attendance, and managing student tuition billing. The implementation results show that the system supports more organized financial management, secure data storage, and automatic generation of financial reports. Additionally, the system provides different access levels according to user roles—such as admin, principal, treasurer, teacher, and parent—thereby promoting collaboration and accountability within the PAUD environment. Abstrak: PAUD Melati 03 merupakan lembaga pendidikan anak usia dini yang memiliki komitmen untuk meningkatkan efektivitas operasional melalui pengelolaan administrasi keuangan yang optimal. Untuk mendukung hal tersebut, diperlukan sistem yang mampu mencatat dan mengelola transaksi keuangan secara efisien dan terstruktur. Penelitian ini bertujuan untuk membangun sistem administrasi keuangan berbasis web guna meningkatkan efisiensi, transparansi, dan keamanan dalam pengelolaan keuangan lembaga. Sistem ini dirancang menggunakan framework Laravel 10 dan Filament untuk memfasilitasi berbagai transaksi keuangan, seperti pencatatan pemasukan dan pengeluaran, penghitungan gaji guru berbasis kehadiran, serta pengelolaan tagihan SPP siswa. Hasil implementasi menunjukkan bahwa sistem mendukung pengelolaan keuangan yang lebih terorganisir, penyimpanan data yang aman, dan pembuatan laporan keuangan secara otomatis. Selain itu, sistem memberikan hak akses berbeda sesuai peran pengguna—seperti admin, kepala sekolah, bendahara, guru, dan wali murid—sehingga mendukung kolaborasi dan akuntabilitas secara optimal di lingkungan PAUD. Kata kunci: Administrasi Keuangan; Sistem Berbasis Web; Laravel; PAUD Melati 03